THE EFFECT OF FINANCIAL LITERACY AND ACCOUNTING LITERACY TO ENTREPRENEURIAL INTENTION USING THEORY OF PLANNED BEHAVIOR MODEL IN STIE SUTAATMADJA ACCOUNTING STUDENTS - Ika Nurbaeti; Sri Mulyati; Bambang Sugiharto (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
Entrepreneurship in Indonesia is still low compared to other countries, but the interest of young people for entrepreneurship is higher. This research was conducted to determine the effect of financial literacy and accounting literacy to entrepreneurial intention by using the theory of planned behavior model. The population used in this study were all active students of accounting study program of STIE Sutaatmadja. Sample selection technique uses simple random sampling. Samples obtained are 150 respondents from semester 2 to semester 8. The analysis tool used in this study is SEM with the help of the LISREL 8.80 program. The results of this study indicate that financial literacy and accounting literacy does not affect the attitude towards new venture creation, subjective norms and perceived behavior control, and subjective norms do not affect the entrepreneurial intention. While the attitude towards new venture creation variable and perceived behavior control affect entrepreneurial intentions